UPAYA PENINGKATAN PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK DENGAN BERMAIN LOMPAT DAN LONCAT - Imam Mustofa Luthfi (MEDIA DIDAKTIKA, 2021)
This study aims to determine the improvement of physical education learning in the subject matter of long jump by playing jump and jump in class V students of Karangsambigalih I Elementary School, Sugio Subdistrict, Lamongan Regency. This research design is a classroom action research that lasts two cycles and in each cycle consists of two meetings. The data was taken before the learning process, during the learning and after learning process. This study was analyzed using quantitative descriptive descriptive techniques. The results of this study indicate that there is an increase in classroom learning and long jump skills by jumping and jumping. The class atmosphere is indicated by the activeness of the results from the first cycle to the second cycle of 100% of children in good category (B) and for the development of 95% prefix long jump basic children in the good category (B), 5% of children in the adequate category. Rejection of 95% of children in good category (B), 5% of children in sufficient category (C). As for landing, 89% of children are in good category (B), 11% of children are in the adequate category (C).